Pleistocene fossil Alcini (Cervidae, Mammalia) from Lombardy and Emilia Romagna (North Italy) - BREDA, Marzia (2002)
Fossil bones of large mammals are frequent in the alluvial deposits of the Po Plain and the moose were known since the beginning of the 19th Century. However a complete and up dated work on the fossil Alcini from Italy was lacking. The numerous new remains shown in this work lead to better outline the distribution of moose in Italy, that shows a palaeobiogeographical meaning. In fact, the Alcini were limited to the Po Plain and never crossed the Apennines to reach Tuscany, which, probably, represented a different bioprovince. The Italian moose remains belong, almost entirely, to the species Alces alces, now living in the northern European regions. Up to now, the extinct genus Cervalces was signalized only twice in our peninsula: from Crostolo Creek near Reggio Emilia (Ambrosetti and Cremaschi, 1976) and from Fornaci di Ranica near Bergamo (Azzaroli, 1979). The specific identification of the Crostolo specimen has been here converted from C. gallicus to C. carnutorum, whether the Ranica remains are confirmed as C. latifrons. Moreover, new finds of both the species are here described: one C. carnutorum from Leffe (Bergamo) and two C. latifrons respectively from San Cipriano Po (Pavia) and from an unknown locality of the Pavese alluvions. The finding of fossil moose alone, cannot lead to a precise palaeoenvironmental reconstruction, however their presence suggests a cold boreal environments with boggy areas dissected by water courses. In Italy, the finding of fossil moose is an index of a cold episode.